Chicken Collagen from Law Market Value By-Products as an Alternate Source. (16th August 2014) - Munasinghe, Kumudini A.; Schwarz, Jurgen G.; Nyame, Anthony K.
Abstract : There has been much interest in investigating possible means of making collagen from underutilized chicken by-products and it will lead to an alternate source of collagen for use in various industries such as pharmaceuticals, cosmetics, biomedical materials, and the food industry. The objective of this research was to find methods to extract collagen from chicken skins and bones to compare the corresponding yield differences and analyze their properties. Collagen extracted by acetic acid, citric acid, alkali, one-step acetic acid and pepsin, and two-step acetic acid and pepsin extraction procedures was compared. Complete randomized design, Student's t -test, and Tukey's test were used to analyze the samples ( P < 0.05 ) . The recovered dry weights for the skin extractions were 6.1, 6.2, 5, 38.7, and 40.4% and those of bone extractions were 4.4, 4.1, 4.1, 19.1, and 20.6%, respectively. Protein, fat, and inorganic material contents of collagen preparations for skin were 62.7%, 1.5%, and 0.7% and for bone were 30.4%, 1.4%, and 0.7%, respectively. This study indicates that chicken by-products have high potential use as an alternate source of collagen.